Pengaruh Strategi Pemasaran Shopee terhadap Perilaku Belanja Konsumen di Indonesia - khorunisa, Atikah Raid; Fadilah, Muinah (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
Rapid technological advances have changed people's shopping habits from physical stores to E-Commerce, with Shopee as one of the platforms that is widely used in Indonesia. This research uses a qualitative descriptive method to analyze Business to Customer (B2C) E-Commerce marketing strategies. The research results show that Shopee makes it easier for business owners to manage their online stores and provides consumers with a comfortable and enjoyable shopping experience. Shopee utilizes various media, such as newspapers, television, magazines and social media, which contribute significantly to increasing product sales on its application, as well as using the Stray Kids brand ambassador to attract the interest of the Indonesian people. In conclusion, Shopee's marketing strategy is effective in improving the shopping and sales experience on their platform.